Low levels of Survival Motor Neuron protein are sufficient for normal muscle function in the SMNΔ7 mouse model of SMA - Iyer, Chitra C. (Hum Mol Genet, 2015)
Spinal Muscular Atrophy (SMA) is an autosomal recessive disorder characterized by loss of lower motor neurons. SMA is caused by deletion or mutation of the Survival Motor Neuron 1 (SMN1) gene and retention of the SMN2 gene. The loss of SMN1 results in reduced levels of the SMN protein. SMN levels appear to be particularly important in motor neurons; however SMN levels above that produced by two copies of SMN2 have been suggested to be important in muscle. Studying the spatial requirement of SMN is important in both understanding how SMN deficiency causes SMA and in the development of effective therapies. Using Myf5-Cre, a muscle-specific Cre driver, and the Cre-loxP recombination system, we deleted mouse Smn in the muscle of mice with SMN2 and SMNΔ7 transgenes in the background, thus providing low level of SMN in the muscle. As a reciprocal experiment, we restored normal levels of SMN in the muscle with low SMN levels in all other tissues. We observed that decreasing SMN in the muscle has no phenotypic effect. This was corroborated by muscle physiology studies with twitch force, tetanic and eccentric contraction all being normal. In addition, electrocardiogram and muscle fiber size distribution were also normal. Replacement of Smn in muscle did not rescue SMA mice. Thus the muscle does not appear to require high levels of SMN above what is produced by two copies of SMN2 (and SMNΔ7).